Manajemen Pembelajaran Daring Program Tahfizh Al-Qur’an Pada Masa Kenormalan Baru Di Al-Wafi Islamic Boarding School - Yusuf Abdullah; Akhmad Shunhaji (Sekolah Tinggi Agama Islam Publisistik Thawalib Jakarta, 2022)
This study aims to determine the management of courageous learning in the tahfizh Al-Qur'an program at Al-Wafi Islamic Boarding School in the new normal. The research was conducted with a case study approach. Collecting data by interview, observation and documentation. Data processing with reduction, displaying data and drawing conclusions. The results showed: (1) learning planning in the form of preparing halaqah tahfizh groups, schedules, methods and learning media. Implementation of learning, combining classical learning with ZOOM and individual learning with WhatsApp. In addition, it is also equipped with learning supervision using Google Sheets. The learning evaluation consists of evaluating the learning process by evaluating and evaluating learning outcomes using a summative evaluation model through semester exams and evaluation through juz incremental exams. (2) Second, the effectiveness of the learning process is seen from two things, first, it is boldly not more effective because it is influenced by students' motivation, students' honesty, parental support at home, teacher competence and adequate facilities. Second, learning applications, WhatsApp and ZOOM Cloud Meeting have high effectiveness and are even the best applications according to their functions. In the Google Spreadsheet application, it is used as an alternative as a tool to create a form of learning tahfizh Al-Qur'an.